LACUNARY STATISTICAL CONVERGENCE OF ORDER ? IN PARTIAL METRIC SPACES - Bayram, Erdal; Bektas, Cigdem A. (Univ Nis, 2023)
The present study introduces the notions of lacunary statistical convergence of order alpha and strongly q- summability of order alpha in partial metric spaces. We examine the inclusion relations linked to these concepts.
Keywords: lacunary statistical convergence; partial metric spaces; inclusion relations